The case of the Shismay Hacienda House - Huánuco and Historical Heritage Management - Lebrún Aspíllaga, Ana María (2020)
The purpose of this article is to inform the community in general about the tourist and cultural attraction of the Casa Hacienda Shismay, after the recovery, enhancement and new cultural use of this architectural work, declared by the National Institute of Culture (Ministry of Culture of Peru) as a historic monument, belonging to the cultural heritage of the nation on July 9, 2008, by National Directorial Resolution N˚ 942/INC. The Casa Hacienda Shismay is located in the San Sebastian de Shismay Village Center, district of Amarilis, province and region of Huanuco, 17 km from the city of Huanuco. This cultural heritage property has valuable cultural and natural assets, now converted into a museum, which became part of a variety of museums that are located within the national territory, presenting the individual and collective memory of their environments, uses and customs, the process of restoration, enhancement, new cultural use and rural tourism proposal that promotes the Casa Hacienda Shismay.